Autophagy : methods and protocols - Ktistakis, Nicholas T.; Florey, Oliver (New York, NY : Humana Press : Springer, 2019)
This volume details a comprehensive and extensive set of protocols for the study of autophagy in vitro and in vivo. Chapters focus on mammals, various model organisms, and provide protocols for the study of autophagy-related processes outside of the canonical autophagy pathways. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Autophagy: Methods and Protocols aims to ensure successful results in the further study of this vital field.
Recombinant expression, purification, and assembly of p62 filaments / Abul K. Tarafder, Audrey Guesdon, Tanja Kuhm, and Carsten Sachse -- Structural studies of autophagy-related proteins / t Imaging noncanonical autophagy and LC3-associated phagocytosis in cultured cells / Elise Jacquin, Katherine Fletcher, and Oliver Florey -- Measurement of bulk autophagy by a cargo sequestration assay / Nikolai Engedal, Morten Luhr, Paula Szalai, and Per O. Seglen -- Methods to detect loss of lysosomal membrane integrity / Sonja Aits -- Monitoring of autophagy and cell volume regulation in kidney epithelial cells in response to fluid shear stress / Maria M. Lazari, Idil Orhon, Patrice Codogno, and Nicolas Dupont -- Identification and regulation of multimeric protein complexes in autophagy via SILAC-based mass spectrometry approaches / t Analysis of autophagy for liver pathogenesis / Nazmul Huda, Hui Zou, Shengmin Yan, Bilon Khambu, and Xiao-Ming Yin -- Autophagy in 3D in vitro and ex vivo cancer models / Carlo Follo, Dario Barbone, William G. Richards,Raphael Bueno, and V. Courtney Broaddus -- Autophagy in platelets / Meenakshi Banerjee, Yunjie Huang, Madhu M. Ouseph, Smita Joshi, Irina Pokrovskaya, Brian Storrie, Jinchao Zhang, Sidney W. Whiteheart, and Qing Jun Wang -- Methods to image macroautophagy in the brain in vivo / Xigui Chen, Kanoh Kondo, and Hitoshi Okazawa -- Measuring nonselective and selective autophagy in the liver / Takashi Ueno and Masaaki Komatsu -- Measuring autophagy in pancreatitis / Alejandro Ropolo, Daniel Grasso, and Maria I. Vaccaro -- Characterization of the "Autophagic Flux" in prostate cancer tissue biopsies by LC3A/LAMP2a immunofluorescence and confocal microscopy / D. Kalamida, A. Giatromanolaki, and M. I. Koukourakis -- Methods to determine the role of autophagy proteins in C. elegans aging / t Imaging the dynamics of mitophagy in live cells / Andrew S. Moore and Erika L. F. Holzbaur -- Triggering mitophagy with photosensitizers / Cheng-Wei Hsieh and Wei Yuan Yang -- Investigating mitophagy and mitochondrial morphology in vivo using mito-QC : a comprehensive guide / Thomas G. McWilliams and Ian G. Ganley -- Assays to monitor mitophagy in Drosophila / Panagiotis Tsapras, Anne-Claire Jacomin, and Ioannis P. Nezis -- Mitophagy dynamics in Caenorhabditis elegans / Konstantinos Palikaras, Eirini Lionaki, and Nektarios Tavernarakis -- Methods for studying mitophagy in yeast / Panagiota Kolitsida and Hagai Abeliovich -- Measuring antibacterial autophagy / Keith B. Boyle and Felix Randow -- Quantitative phosphoproteomics of selective autophagy receptors / Thomas Juretschke, Petra Beli, and Ivan Dikic -- Analysis of chaperone-mediated autophagy / Y. R. Juste and A. M. Cuervo -- Interactive autophagy : monitoring a novel form of selective autophagy by macroscopic observations / Jana Petri and Roland L. Knorr.
Includes bibliographical references and index.
Online resource; title from PDF title page (SpringerLink, viewed January 7, 2019).
Keywords: Cell death -- Laboratory manuals; Apoptosis -- Laboratory manuals; Autophagy; Cellules -- Mort -- Manuels de laboratoire; Apoptose -- Manuels de laboratoire; Autophagie (Cytologie); Apoptosis; Cell death; Laboratory Manual; Laboratory manuals; Laboratory manuals; Manuels de laboratoire